Identification of phenolic acids and flavonoids in monofloral honey from Bangladesh by high performance liquid chromatography: detemination of antioxidant capacity - Moniruzzaman, M.; Yung An, C.; Rao, P.V.; Hawlader, M.N.I.; Azlan, S.A.B.M.; Sulaiman, S.A.; Gan, S.H, (2014)
The aim of the present study was to characterize the phenolic acids, flavonoids, and antioxidant properties of monofloral honey collected from five different districts in Bangladesh. A new high performance liquid chromatography (HPLC) equipped with a UV detector method was developed for the identification of the phenolic acids and flavonoids. A total of five different phenolic acids were identified, with the most abundant being caffeic acid, benzoic acid, gallic acid, followed by chlorogenic acid and trans-cinnamic acid. The flavonoids, kaempferol, and catechin were most abundant, followed by myricetin and naringenin. The mean moisture content, total sugar content, and color characteristics of the honey samples were 18.36 ± 0.95%, 67.40 ± 5.63 g/100 g, and 129.27 ± 34.66 mm Pfund, respectively. The mean total phenolic acids, total flavonoid content, and proline content were 199.20 ± 135.23, 46.73 ± 34.16, and 556.40 ± 376.86 mg/kg, respectively, while the mean FRAP values and DPPH radical scavenging activity were 327.30 ± 231.87 μM Fe (II)/100 g and 36.95 ± 20.53%, respectively. Among the different types of honey, kalijira exhibited the highest phenolics and antioxidant properties. Overall, our study confirms that all the investigated honey samples are good sources of phenolic acids and flavonoids with good antioxidant properties